Rancang Bangun Aplikasi Clinical Telereporting Dengan Prinsip Database As A Service - Regar, Fretie Dwirory Magdalena Anggraih; Sutanto, Teguh; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: PT. Indonesia Japan Medical Instrumentation (PT. JIMI) in collaboration with several health centers in Indonesia, such as by a clinic in Tulungagung and Klinik Catur Warga (KCW) in Mataram. Cooperation of both sides of the related procurement of Magnetic Resonance Imaging (MRI). PT. JIMI as an investor MRI and KCW as a user and the owner of the asset. Joint Operation between PT. JIMI and KCW requires KCW applied to report the amount of MRI usage and the income derived from the operation of the MRI. KCW reported it every month. PT. JIMI as investors need to anticipate the possibility of fraud in reporting is done KCW. Cheating in question is related to the amount of data manipulation tool use MRI and income derived from the operation of the tool. In case of manipulation of the data in the report will have an impact on the results received nominal PT. JIMI. So that would inhibit PT. JIMI as soon as possible to restore the initial capital they have invested. Of the possibility of reporting fraud committed KCW, PT. JIMI need for monitoring directly related to the operation of the MRI theirs. Based on the description above problems, then made a telereporting clinical applications integrated with PACS and Medview® Medview® existing Cloud. Telereporting clinical application consists of two parts, namely the Report Server and Report Client. Report Client side access patient data stored MRI examination results in Medview® Cloud. Report Server to access the database side Medview® PACS based on log data and patient examination data.